Combustion kinetics of wet-torrefied forest residues using the distributed activation energy model (DAEM). (1st January 2017) - Bach, Quang-Vu; Tran, Khanh-Quang; Skreiberg, Øyvind
Highlights: Wet torrefaction enhances the devolatilization reactivity of forest residues, but too severe conditions reverse the trend. Forest residues are more reactive in the combustion stage after wet torrefaction. The distributed activation energy model (DAEM) is employed for kinetics analysis. The activation energy and pre-exponential factors of cellulose and lignin are increased by wet torrefaction. Wet torrefaction increases the mass fraction but decreases the kinetic parameters of char. Abstract: This study was carried out to evaluate the effects of wet torrefaction (WT) on the combustion reactivity and kinetics of Norwegian forest residues. The wet torrefaction temperature was varied at 175, 200, or 225 °C. The combustion of the raw and torrefied forest residues was thermogravimetrically studied in synthetic air (21% O2 and 79% N2 in volume). The distributed activation energy model (DAEM) with four parallel reactions was adopted for the kinetic analysis. The results show that WT enhances the devolatilization reactivity of the forest residues, but too severe conditions reverse the trend. Moreover, torrefied forest residues are more reactive, and exhibit a broader and longer combustion stage than the raw residues. The extracted kinetic data confirm the removal of hemicellulose from the forest residues after WT. The kinetic parameters of cellulose and lignin increase after WT. In addition, the mass fraction of char is increased gradually with WT severity while its kinetic parameters are decreased by WT.